Additive Manufacturing of 3D Luminescent ZrO2:Eu3+ Architectures - Winczewski, Jędrzej; Herrera, Manuel; Cabriel, Clément; Izeddin, Ignacio; Gabel, Stefan; Merle, Benoit; Susarrey Arce, Arturo; Gardeniers, Han (Advanced Optical Materials, 2022)
Implementation of more refined structures at the nano to microscale is expected to advance applications in optics and photonics. This work presents the additive manufacturing of 3D luminescent microarchitectures emitting light in the visible range. A tailor-made organo-metallic resin suitable for two-photon lithography is developed, which upon thermal treatment in an oxygen-rich atmosphere allows the creation of silicon-free tetragonal (t-) and monoclinic (m-) ZrO2. The approach is unique because the tailor-made Zr-resin is different from what is achieved in other reported approaches based on sol−gel resins. The Zr-resin is compatible with the Eu-rich dopant, a luminescent activator, which enables to tune the optical properties of the ZrO2 structures upon annealing. The emission characteristics of the Eu-doped ZrO2 microstructures are investigated in detail with cathodoluminescence and compared with the intrinsic optical properties of the ZrO2. The hosted Eu has an orange−red emission showcased using fluorescence microscopy. The presented structuring technology provides a new platform for the future development of 3D luminescent devices.
CRIS-Team Scopus Importer:2022-05-06
Keywords: additive manufacturing; europium; luminescence; two-photon lithography; zirconia

Additive manufacturing of 3D yttria-stabilized zirconia microarchitectures - Winczewski, J. P.; Zeiler, Stefan; Gabel, Stefan; Maestre, D.; Merle, Benoit; Gardeniers, J. G.E.; Susarrey Arce, A. (Materials and Design, 2024)
The additive manufacturing (AM) of yttria-stabilized zirconia (YSZ) microarchitectures with sub-micrometer precision via two-photon lithography (TPL), utilizing custom photoresin containing zirconium and yttrium monomers is investigated. YSZ 3D microarchitectures can be formed at low temperatures (600 °C). The low-temperature phase stabilization of ZrO2 doped with Y2O3 demonstrates that doping ZrO2 with ≈ 10 mol% Y2O3 stabilizes the c-ZrO2 phase. The approach does not utilize YSZ particles as additives. Instead, the crystallization of the YSZ phase is initiated after printing, i.e., during thermal processing in the air at 600 °C – 1200 °C for one and two hours. The YSZ microarchitectures are characterized in detail. This includes understanding the role of defect chemistry, which has been overlooked in TPL-enabled micro-ceramics. Upon UV excitation, defect-related yellowish-green emission is observed from YSZ microarchitectures associated with intrinsic and extrinsic centers, correlated with the charge compensation due to Y3+ doping. The mechanical properties of the microarchitectures are assessed with manufactured micropillars. Micropillar compression yields the intrinsic mechanical strength of YSZ. The highest strength is observed for micropillars annealed at 600 °C, and this characteristic decreased with an increase in the annealing temperature. The deformation behavior gradually changes from ductile to brittle-like, correlating with the Hall–Petch strengthening mechanism.
CRIS-Team Scopus Importer:2024-04-05
Keywords: 3D printing; Additive manufacturing; Micromechanics; Photoluminescence; Yttria-stabilized zirconia

A new method for microscale cyclic crack growth characterization from notched microcantilevers and application to single crystalline tungsten and a metallic glass - Gabel, Stefan; Merle, Benoit; Bitzek, Erik; Göken, Mathias (Journal of Materials Research, 2022)
Keywords: kernfusionsrelevant

Evaluation of the surface fatigue behavior of amorphous carbon coatings through cyclic nanoindentation - Weikert, Tim; Wartzack, Sandro; Baloglu, Maximilian Volkan; Willner, Kai; Gabel, Stefan; Merle, Benoit; Pineda, Fabiola; Walczak, Magdalena; Marian, Max; Rosenkranz, Andreas; Tremmel, Stephan (Surface & Coatings Technology, 2021)
Diamond-like carbon (DLC) coatings, frequently used to reduce wear and friction in machine components as well as on forming tools, are often subjected to cyclic loading. Doping of DLC coatings with metals or metal carbides as well as the usage of multilayer architectures represent promising approaches to enhance toughness, which is beneficial for the coatings’ behavior under cyclic loading. In this study, we utilized cyclic nanoindentation to characterize the tribologically induced surface fatigue behavior of single-layer tungsten-doped (a-C:H:W) and multilayer silicon oxide containing (a-C:H:Si:O/a-C:H)25 amorphous carbon coatings under cyclic loading. Columnar growth was observed for both coatings by focused ion beam microscopy and scanning electron microscopy, while the multilayer architecture of the (a-C:H:Si:O/a-C:H)25 coating was verified by the silicon content using glow-discharge optical emission spectroscopy. In cyclic nanoindentation of the (a-C:H:Si:O/a-C:H)25 multilayer coating, stepwise small changes in indentation depth were observed over several indentation cycles. The surface fatigue process of the single-layer a-C:H:W covered a smaller number of indentation cycles and was characterized by an early steep increase of the static displacement signal. Microscopical analyses hint at grain deformation, sliding at columnar boundaries, and grain detachment as underlying fatigue mechanisms of the a-C:H:W coating, while the (a-C:H:Si:O/a-C:H)25 multilayer coating showed transgranular crack propagation and gradual fracturing. In case of the (a-C:H:Si:O/a-C:H)25 multilayer coating, superior indentation hardness (HIT) and indentation modulus (EIT) as well as a higher HIT3/EIT2 ratio suggest a higher resistance to plastic deformation. A high HIT3/EIT2 ratio, being an indicator for hindered crack initiation, combined with the capability of stress relaxation in soft layers contributed to the favorable surface fatigue behavior of the (a-C:H:Si:O/a-C:H)25 multilayer coating observed in this cyclic nanoindentation studies.
Keywords: Diamond-like carbon; Cyclic nanoindentation; Surface fatigue; Multilayer architecture

Exploring the mechanical properties of additively manufactured carbon-rich zirconia 3D microarchitectures - Winczewski, J. P.; Zeiler, Stefan; Gabel, Stefan; Susarrey-Arce, A.; Gardeniers, J. G.E.; Merle, Benoit (Materials & Design, 2023)
Two-photon lithography (TPL) is a promising technique for manufacturing ceramic microstructures with nanoscale resolution. The process relies on tailor-made precursor resins rich in metal–organic and organic constituents, which can lead to carbon-based residues incorporated within the ceramic microstructures. While these are generally considered unwanted impurities, our study reveals that the presence of carbon-rich residues in the form of graphitic and disordered carbon in tetragonal (t-) ZrO2 can benefit the mechanical strength of TPL microstructures. In order to achieve a better understanding of these effects, we deconvolute the structural and materials contributions to the strength of the 3D microarchitectures by comparing them to plain micropillars. We vary the organic content by different thermal treatments, resulting in different crystal structures. The highest compression strength of 3.73 ± 0.21 GPa and ductility are reached for the t-ZrO2 micropillars, which also contain the highest carbon content. This paradoxical finding opens up new perspectives and will foster the development of “brick and mortar”-like ceramic microarchitectures.
CRIS-Team Scopus Importer:2023-07-28
Keywords: 3D printing; Additive manufacturing; Micromechanics; Micropillar compression; Zirconia

Microcantilever Fracture Tests of α-Cr Containing NiAl Bond Coats - Gabel, Stefan; Giese, Sven; Webler, Ralf; Neumeier, Steffen; Göken, Mathias (Advanced Engineering Materials, 2022)
MCrAlY bond coats are widely used as oxidation-resistant coatings on superalloys. The major phase is the thermally stable intermetallic β-NiAl phase. The addition of Cr increases the oxidation and corrosion resistance but leads to the formation of α-Cr precipitates. Both phases are brittle and limit the fracture toughness of these coatings. To study the influence of thermal exposure and the resulting changing chemical composition on the fracture properties, the fracture toughness of both phases is measured by notched microcantilever bending, after processing and after oxidation by thermal cycling. The fracture toughness of β-NiAl decreases during thermal cycling due to the depletion in Al, whereas the fracture toughness and the composition of α-Cr stay constant. As the fracture toughness of α-Cr is lower compared with β-NiAl, the formation of α-Cr precipitates is supposed to decrease the fracture toughness of the bond coat.
CRIS-Team Scopus Importer:2022-01-28

Microcantilever Fracture Tests on Eutectic NiAl–Cr(Mo) In Situ Composites - Gabel, Stefan; Giese, Sven; Merle, Benoit; Sprenger, Ioannis; Heilmaier, Martin; Neumeier, Steffen; Bitzek, Erik; Göken, Mathias (Advanced Engineering Materials, 2021)
Lamellar eutectic NiAl–Cr(Mo) alloys show an increased fracture toughness due to different toughening mechanisms. These mechanisms result from the fibrous or lamellar microstructure of the two constituting phases α-Cr(Mo) and β-NiAl. However, the fracture toughness of the individual phases and the evolution from early crack growth to the toughening mechanisms have not yet been systematically studied. Herein, bending tests on focused ion beam (FIB)-notched microcantilever beams are used to characterize the small-scale fracture properties. The micromechanical investigations reveal that the fracture toughness of the α-Cr(Mo) phase ((Formula presented.)) is much higher than the fracture toughness of β-NiAl ((Formula presented.)). Larger cantilevers in the crack arresting orientation show an enhanced fracture toughness with up to (Formula presented.), which is still lower than the one of macroscopic experiments. This is attributed to the small interaction volume of the crack, which hinders the full exploitation of potential extrinsic toughening mechanisms.
CRIS-Team Scopus Importer:2021-03-19
Keywords: eutectic alloys; focused ion beam; fractures; intermetallic; micromechanics

Novel Class of Rhenium Borides Based on Hexagonal Boron Networks Interconnected by Short B2Dumbbells - Bykova, Elena; Johansson, Erik; Bykov, Maxim; Chariton, Stella; Fei, Hongzhan; Ovsyannikov, Sergey V.; Aslandukova, Alena; Gabel, Stefan; Holz, Hendrik; Merle, Benoit; Alling, Björn; Abrikosov, Igor A.; et al. (Chemistry of Materials, 2022)
Transition metal borides are known due to their attractive mechanical, electronic, refractive, and other properties. A new class of rhenium borides was identified by synchrotron single-crystal X-ray diffraction experiments in laser-heated diamond anvil cells between 26 and 75 GPa. Recoverable to ambient conditions, compounds rhenium triboride (ReB3) and rhenium tetraboride (ReB4) consist of close-packed single layers of rhenium atoms alternating with boron networks built from puckered hexagonal layers, which link short bonded ( 1.7 Å) axially oriented B2 dumbbells. The short and incompressible Re-B and B-B bonds oriented along the hexagonal c-axis contribute to low axial compressibility comparable with the linear compressibility of diamond. Sub-millimeter samples of ReB3 and ReB4 were synthesized in a large-volume press at pressures as low as 33 GPa and used for material characterization. Crystals of both compounds are metallic and hard (Vickers hardness, HV = 34(3) GPa). Geometrical, crystal-chemical, and theoretical analysis considerations suggest that potential ReBx compounds with x > 4 can be based on the same principle of structural organization as in ReB3 and ReB4 and possess similar mechanical and electronic properties.
CRIS-Team Scopus Importer:2022-09-30

Small-scale high-cycle fatigue testing by dynamic microcantilever bending - Gabel, Stefan; Merle, Benoit (MRS Communications, 2020)
The lifetime of cyclically loaded devices is often limited by the fatigue resistance of their individual phases. An advanced method is presented for measuring the high-cycle fatigue behavior of materials at the micrometer scale using a nanoindenter. It is based on the cyclic deflection of focused ion beam-fabricated microcantilevers using the continuous stiffness method (CSM). In line with experimental data on bulk nanocrystalline copper, the specimens exhibit grain coarsening followed by the formation of extrusions and a fatigue strength exponent of -0.10. The method is suitable for characterizing single phases and individual components of further complex systems.
CRIS-Team Scopus Importer:2020-05-12

Synthesis, crystal structure, and properties of stoichiometric hard tungsten tetraboride, WB4 - Bykova, Elena; Ovsyannikov, Sergey; Bykov, Maxim; Yin, Yuqing; Fedotenko, Timofey; Holz, Hendrik; Gabel, Stefan; Merle, Benoit; Chariton, Stella; Prakapenka, Vitali B.; Dubrovinskaia, Natalia; Goncharov, Alexander F.; et al. (Journal of Materials Chemistry A, 2022)
Tungsten tetraboride has been known so far as a non-stoichiometric compound with a variable composition (e.g. WB4-x, WB4+x). Its mechanical properties could exceed those of hard tungsten carbide, which is widely used nowadays in science and technology. The existence of stoichiometric WB4 has not been proven yet, and its structure and crystal chemistry remain debatable to date. Here we report the synthesis of single crystals of the stoichiometric WB4 phase under high-pressure high-temperature conditions. The crystal structure of WB4 was determined using synchrotron single-crystal X-ray diffraction. In situ high-pressure compressibility measurements show that the bulk modulus of WB4 is 238.6(2) GPa for B ' = 5.6(0). Measurements of mechanical properties of bulk polycrystalline sub-millimeter size samples under ambient conditions reveal a hardness of similar to 36 GPa, confirming that the material falls in the category of superhard materials.
CRIS-Team WoS Importer:2022-09-09

The influence of crack and interface oxidation on dwell fatigue crack propagation behavior of the nickel-base superalloy ATI A718Plus - Kirchmayer, Andreas; Hausmann, Andreas; Gabel, Stefan; Pröbstle, Martin; Giese, Sven; Göken, Mathias; Hünert, Daniela; Neumeier, Steffen (Metallurgical and Materials Transactions A-Physical Metallurgy and Materials Science, 2024)
The crack propagation properties are an important and often limiting factor for the commercial application of superalloys in aerospace applications where the oxidation ahead of the crack tip plays an important role. Previous research on the Ni-base superalloy A718Plus revealed that the orientation and the volume fraction of the high temperature grain boundary phases δ and η have a major influence on the dwell fatigue crack propagation rate at 650 °C in ambient air but not in vacuum. In this work, the effect of internal oxidation at the η/δ–matrix interface and its effect on dwell fatigue crack propagation and mechanical properties are examined by advanced microscopic methods and micro-cantilever testing. During crack propagation, the crack tip is exposed to air where a Nb-rich oxide layer forms and embrittles the η/δ–matrix interface causing the cracks to deflect and propagate along the oxidized interfaces. Micro-cantilever tests on the oxidized interface show that these oxide layers also significantly reduce the local strength and fracture toughness of the material. This proves that interfacial oxide layers are the underlying reason for the reduction of the dwell fatigue crack growth resistance at 650 °C, particularly in microstructures whose η/δ–matrix interfaces are oriented parallel to the crack growth direction.<br

The influence of crack and interface oxidation on dwell fatigue crack propagation behavior of the nickel-base superalloy ATI A718Plus - Kirchmayer, Andreas; Hausmann, Daniel; Gabel, Stefan; Pröbstle, Martin; Giese, Sven; Göken, Mathias; Hünert, Daniela; Neumeier, Steffen (Metallurgical and Materials Transactions A-Physical Metallurgy and Materials Science, 2024)
The crack propagation properties are an important and often limiting factor for the commercial application of superalloys in aerospace applications where the oxidation ahead of the crack tip plays an important role. Previous research on the Ni-base superalloy A718Plus revealed that the orientation and the volume fraction of the high temperature grain boundary phases δ and η have a major influence on the dwell fatigue crack propagation rate at 650 °C in ambient air but not in vacuum. In this work, the effect of internal oxidation at the η/δ–matrix interface and its effect on dwell fatigue crack propagation and mechanical properties are examined by advanced microscopic methods and micro-cantilever testing. During crack propagation, the crack tip is exposed to air where a Nb-rich oxide layer forms and embrittles the η/δ–matrix interface causing the cracks to deflect and propagate along the oxidized interfaces. Micro-cantilever tests on the oxidized interface show that these oxide layers also significantly reduce the local strength and fracture toughness of the material. This proves that interfacial oxide layers are the underlying reason for the reduction of the dwell fatigue crack growth resistance at 650 °C, particularly in microstructures whose η/δ–matrix interfaces are oriented parallel to the crack growth direction.
CRIS-Team Scopus Importer:2024-02-16

Understanding creep of a single-crystalline Co-Al-W-Ta superalloy by studying the deformation mechanism, segregation tendency and stacking fault energy - Volz, Nicklas; Xue, Fei; Zenk, Christopher; Bezold, Andreas; Gabel, Stefan; Subramanyam, A. P.A.; Drautz, R.; Hammerschmidt, T.; Makineni, S. K.; Gault, B.; Göken, Mathias; Neumeier, Steffen (Acta Materialia, 2021)
A systematic study of the compression creep properties of a single-crystalline Co-base superalloy (Co-9Al-7.5W-2Ta) was conducted at 950, 975 and 1000°C to reveal the influence of temperature and the resulting diffusion velocity of solutes like Al, W and Ta on the deformation mechanisms. Two creep rate minima are observed at all temperatures indicating that the deformation mechanisms causing these minima are quite similar. Atom-probe tomography analysis reveals elemental segregation to stacking faults, which had formed in the γ′ phase during creep. Density-functional-theory calculations indicate segregation of W and Ta to the stacking fault and an associated considerable reduction of the stacking fault energy. Since solutes diffuse faster at a higher temperature, segregation can take place more quickly. This results in a significantly faster softening of the alloy, since cutting of the γ′ precipitate phase by partial dislocations is facilitated through segregation already during the early stages of creep. This is confirmed by transmission electron microscopy analysis. Therefore, not only the smaller precipitate fraction at higher temperatures is responsible for the worse creep properties, but also faster diffusion-assisted shearing of the γ′ phase by partial dislocations. The understanding of these mechanisms will help in future alloy development by offering new design criteria.<br
Keywords: Co-base superalloys; Directional coarsening; Creep; Stacking fault energy; DFT